2006
DOI: 10.1021/ie0602097
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Amino Acids:  Influence of the pH value and the Addition of Alcoholic Cosolvents on Aqueous Solubility

Abstract: The solubility of DL-methionine in pure water has been measured in a temperature range of 293.15-353.15 K by means of on-line attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy. These experimental data, as well as literature data for the solubility of glycine and DL-alanine in aqueous and alcohol solutions, were modeled using the PC-SAFT equation of state. Pure-component parameters for glycine, DL-alanine, and DL-methionine were fitted to the vapor pressures and to the densities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
176
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 32 publications
2
176
1
2
Order By: Relevance
“…These parameters are applied to predict single-sugar solubility in pure solvents (water, ethanol, or methanol) and in solvent mixtures (water/ethanol, water/methanol) as well as osmotic coefficients in aqueous solutions containing two or more sugars. This study uses the Perturbed-Chain Statistical Association Fluid Theory (PC-SAFT) framework because it has already proven flexibility and performance in modeling complex systems containing biomolecules (amino acids, [14][15][16] osmolytes, 17 urea 18 ) as well as electrolytes [19][20][21][22] in aqueous solutions. The pure-component parameters of the sugars were determined by fitting to experimental solution densities and osmotic coefficients of binary sugar/water mixtures only.…”
mentioning
confidence: 99%
“…These parameters are applied to predict single-sugar solubility in pure solvents (water, ethanol, or methanol) and in solvent mixtures (water/ethanol, water/methanol) as well as osmotic coefficients in aqueous solutions containing two or more sugars. This study uses the Perturbed-Chain Statistical Association Fluid Theory (PC-SAFT) framework because it has already proven flexibility and performance in modeling complex systems containing biomolecules (amino acids, [14][15][16] osmolytes, 17 urea 18 ) as well as electrolytes [19][20][21][22] in aqueous solutions. The pure-component parameters of the sugars were determined by fitting to experimental solution densities and osmotic coefficients of binary sugar/water mixtures only.…”
mentioning
confidence: 99%
“…Meanwhile, chemical analyses suggest that the protein-like fluorophores consist primarily of proteinaceous materials (e.g., proteins and peptides; Yamashita and Tanoue, 2003;Maie et al, 2007), and this DOC fraction is generally hydrophilic and low molecular weight (LMW) compounds (e.g., Sommerville and Preston, 2001). Results of Chen et al (1989) and Fuchs et al (2006) showed that solubility of the proteinaceous materials in LMW is generally affected by neither pH within the normal range of 6-9 nor colloid coagulation. Therefore, increasing ionic strength (or salinization) can enhance the solubility of the proteinaceous materials via sodium dispersion (Green et al, 2008(Green et al, , 2009a or through nonspecific electrostatic interactions at low salinities (called a "salting-in" effect) (Tanford, 1961;Chen et al, 1989).…”
Section: S Duan and S S Kaushal: Salinization Alters Fluxes Of Biomentioning
confidence: 97%
“…The high peptide-binding ability of DBC can be attributed to both covalent and noncovalent interactions with Col-p. There is also an increase in the uncharged amino groups (NH 2 ) of amino acids with increased pH, 30 such as lysine and arginine, which enables Col-p to be immobilized on DBC through aldehyde groups. It is well known that aldehydic groups can covalently cross-link with collagen by amino functional groups of the protein.…”
Section: Effects Of Do Ph and Zeta Potential On Peptide-bindingmentioning
confidence: 99%